Advanced topics in signal processing - Lim, Jae S. (Prentice Hall, 1988)
Designed for Advanced Topics in DSP Courses. Text consists of 8 chapters with each chapter covering a specific advanced topic. Topics include: parametric signal modeling, spectral estimation, multirate signal processing, Fourier transform and convolution algorithms, adaptive signal processing.